2013
DOI: 10.1080/00063657.2013.809048
|View full text |Cite
|
Sign up to set email alerts
|

Testing assumptions of a supplementary feeding experiment aimed at suburban House SparrowsPasser domesticus

Abstract: Capsule Empirical support is provided for the design and field methods associated with a replicated supplementary feeding experiment.Aims We tested assumptions associated with a supplementary feeding experiment in which counts of House Sparrows were used to infer impacts of feeding mealworms and seed on reproductive output and population size. Methods Supplementary food was provided at 33 House Sparrow colonies spread across suburban London, with 33 unfed colonies serving as controls. We compared the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…The samples of fed and unfed colonies were similar with respect to geographical location, habitat character (including the extent of green space and housing density), initial colony size, background supplementary feeding by residents (mainly seed) and density of domestic cats (Peach et al . ). The distances between study colonies (mean and minimum nearest neighbour distances between fed and unfed colonies were 2.89 and 1.29 km, respectively) were large enough to ensure that provisioning adults from unfed colonies did not have access to our mealworms (Heij & Moeliker , Bower , Shaw ).…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…The samples of fed and unfed colonies were similar with respect to geographical location, habitat character (including the extent of green space and housing density), initial colony size, background supplementary feeding by residents (mainly seed) and density of domestic cats (Peach et al . ). The distances between study colonies (mean and minimum nearest neighbour distances between fed and unfed colonies were 2.89 and 1.29 km, respectively) were large enough to ensure that provisioning adults from unfed colonies did not have access to our mealworms (Heij & Moeliker , Bower , Shaw ).…”
Section: Methodsmentioning
confidence: 97%
“…Surveys of feeder usage indicated that 96% of mealworms were taken by House Sparrows, 70% being taken by adults (60% carried away, 10% eaten) and 26% by juveniles or females (12% carried away, 14% eaten; Peach et al . ). Of the 60% of total mealworms carried away by adult Sparrows, 35% were carried by females and 25% by males.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations